PROBLEMATIKA PEMBELAJARAN PAI DAN UPAYA MENGATASINYA - Fatimatuz Zahra; Umi Habibah; Nurela Nurela (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2024)
In the learning process there will definitely be a problem, whether it is a problem from outside or a problem from within the students. Problems in learning are not only found in the school environment but the family environment and community environment can also become problems in student learning, when the environment is not in accordance with educational expectations, all of this is very influential in the success of students' learning. The aim of this research is to find out the problems of PAI learning and solutions to overcome these problems. This research uses a literature review method with a content analysis approach. The results of this research are: There are three environments that cause problems in learning, namely the school environment, family and community. Problems in the school environment include low student interest in learning, problems from educators themselves, namely the use of monotonous methods, inadequate teacher quality, incomplete facilities and infrastructure, and the learning methods used do not emphasize student activity. Problems in the family environment include parenting styles or the way parents educate their children, parent-child relationships, disharmonious family atmosphere, and unsupportive economic factors. Meanwhile, the problem with society is having toxic friends, namely friends who always look for other people's faults, don't want to be blamed, feel they are right, are lazy, have negativity and so on.